KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII DI SMP ASSALAM PONTIANAK BARAT - Yulira, Bernicha Sita Sherlina; Syam, Christanto; Seli, Sesillia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research is to determine "Ability to Write Text Reports on Observation Results of Class VII Students of Assalam Middle School, West Pontianak". Descriptive research method with a quantitative approach. The sample for this research consisted of 38 people. Data collection techniques use test techniques (essay questions). The ability to write observation report text is assessed from the structural aspect, linguistic rules aspect, as well as spelling and punctuation aspects. The data analysis technique used is simple statistics by determining validity and reliability and calculating the average value of students' writing ability in the observation report text. The results of the research show that the average score for the ability to write observation report text for class VII students at Assalam West Pontianak Middle School from the structural aspect obtained an average score of 53.55, which means it is included in the poor category, from the aspect of linguistic rules. , the average score is 57.36 which means it is in the poor category, and from the aspect of spelling use (EYD) it gets an average score of 96 which means it is included in the very capable category. Based on the Maximum Completeness Criteria, those who obtained a score below 70 or below the KKM were 23 students with a percentage of (60.53%) and students who were able to write observation report texts were only 15 students with a percentage of (39.47%). In conclusion, students are still lacking in writing observation report texts.